Reflections of children's stress in the teaching and learning process: possibilities of pedagogical intervention (Research, Society and Development, 2021)
This study aims to analyze how child stress is reflected in the teaching and learning process, especially in the early years of basic education. Stress is a physical and psychological reaction that affects individuals, negatively or positively, at any age, including children. This research stems from the concern to understand the relationship between stress and students' school performance, analyzing the causes and symptoms arising from childhood stress. Child stress can interfere with the child's development, socialization and learning process, as it reduces the learner's concentration and self-esteem, as well as their interaction with the surrounding world. Thus, the teaching intervention is important in the process of identifying stress disorder pictures, as it may provide the basis and help for students to develop and deal with the stressful situations to which they are subjected. In view of the above, the importance of understanding the stress symptoms presented by children early is reinforced, so that adults can intervene to help overcome these difficulties and prevent severe cognitive, emotional and even physical consequences, and it is up to the teacher. Provide a harmonious environment that allows students to learn in a meaningful and peaceful way, reducing the stressful sources and consequences of child stress.